Opioids With or Without Low-Dose Naloxone During the Perioperative Period: A Systematic Review With Meta-Analysis - Benyu Mao; Xian Wang; Xianping Zhang; Min Chen (Pain Research and Management)
Conclusions: Our findings show that the use of low-dose naloxone in combination with opioids can lower the risk of somnolence and coughing, postoperative nausea, and vomiting.